Self-rating via video communication in children with disability – a feasibility study - Ivarsson, Magnus; Andersson, Anna Karin; Almqvist, Lena (Frontiers in Psychology, 2023)
Background: Different barriers may hinder children with developmental disabilities (DD) from having a voice in research and clinical interventions concerning fundamentally subjective phenomena, such as participation. It is not well-investigated if video communication tools have the potential to reduce these barriers. Aim: This study investigated the feasibility of administering a self-rating instrument measuring participation, Picture My Participation (PmP), via a video communication tool (Zoom), to children with DD. Materials and methods: PmP was administered to 17 children with DD (mean age 13 years). The pictorial representations of activities and response options in PmP were displayed in a shared PowerPoint presentation, enabling nonverbal responses with the annotate function in Zoom. Child and interviewer perceptions of the interview were measured through questionnaires developed for the purpose. Results: All the children completed the interview. Most PmP questions were answered, and no adverse events were registered. Technical issues could generally be solved. No special training or expensive equipment was needed for the interviews. Conclusion: Interviewer-guided self-ratings of participation and related constructs through video communication may be a feasible procedure to use with children with DD from age 11. Significance: Offering video communication may increase children’s chances to contribute subjective experiences in research and clinical practice.